Regional Integration and the challenges of Intra-Regional Trade : an assessment of the implementation of SADC's Free Trade Agreement - Nshimbi, Christopher Changwe (University of Pretoria, 2018)
Mini Dissertation (MA)--University of Pretoria, 2017.